2018
DOI: 10.1097/nmd.0000000000000810
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward Disclosing a Mental Health Problem and Reemployment

Abstract: Despite low unemployment rates, individuals with mental health problems often struggle to gain reemployment. Many face the decision whether to disclose their mental illness to employers. This study therefore examined the role of disclosure attitudes for reemployment over time. Clinical and job search variables as well as attitudes toward disclosing a mental health issue to an employer were assessed among 301 unemployed individuals with mental health problems. Predictors of reemployment at 6-month follow-up wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 10 publications
3
20
0
2
Order By: Relevance
“…The finding that employment specialists are in favour of and encourage their clients' disclosure has also been found by others [24,25]. In line with what respondents generally believed, several studies have shown that disclosure during the hiring period resulted in fewer invitations for job interviews [10], and that greater reluctance to disclose mental illness increased chances of reemployment after 6 months, [26]. There are several explanations for this deviant opinion of work reintegration professionals.…”
Section: Discussionsupporting
confidence: 52%
“…The finding that employment specialists are in favour of and encourage their clients' disclosure has also been found by others [24,25]. In line with what respondents generally believed, several studies have shown that disclosure during the hiring period resulted in fewer invitations for job interviews [10], and that greater reluctance to disclose mental illness increased chances of reemployment after 6 months, [26]. There are several explanations for this deviant opinion of work reintegration professionals.…”
Section: Discussionsupporting
confidence: 52%
“…A high number of employers (72%) have been found to believe that potential employees should disclose MI/MHI prior to recruitment [25]. However, studies have shown that if employers are aware of job applicants' mental health conditions, they are less inclined to hire them [26,27].…”
Section: Social Stigma Definedmentioning
confidence: 99%
“…Another advantage of disclosure is that it enables authenticity (i.e., employees' ability to act in accordance with their true selves) [27,36] in the work environment. Authenticity has been shown to be positively related to work engagement, job satisfaction and work performance [36].…”
Section: Social Stigma Definedmentioning
confidence: 99%
“…In einer feindseligen Umgebung dürften die Nachteile von Offenlegung überwiegen, umgekehrt ermöglicht Offenlegung oft erst soziale Unterstützung. So fanden wir unter psychisch erkrankten Arbeitslosen, dass Offenlegung der eigenen Erkrankung bei der Arbeitsuche im Verlauf einerseits das Finden einer neuen Arbeitstelle erschwert [6], andererseits Offenlegung im privaten Bereich die Lebensqualität verbessert [25]. Insgesamt sprechen empirische Befunde dafür, dass Offenlegung der eigenen psychischen Erkrankung zu besserer Lebensqualität und sozialer Unterstützung führt [24], die Entscheidung für den Einzelnen bleibt aber angesichts des Risikos der Diskriminierung komplex und situationsabhängig.…”
Section: Offenlegungunclassified